Evaluation of acute oral toxicity, cytotoxicity, antidepressant and antioxidant activities of Japanese mint (Mentha arvensis L.) oil - Tanjina Yousuf; Rasheda Akter; Jamiuddin Ahmed; Santosh Mazumdar; Debashish Talukder; Nemai Chandra Nandi; Mohammad Nurulamin (Elsevier, 2021)
ABSTRACT: Background: Menthol-rich essential oil of Mentha arvensis L. (Japanese mint) have been identified as a valuable and new source of natural bioactive compounds with applications not only in industry but also in our daily life. Objective: The present study aimed to assess the cytotoxicity, acute toxicity, antidepressant and antioxidant activities of Japanese mint oil (JMO). Methods: Brine shrimp lethality assay was performed to investigate cytotoxicity of JMO. The acute toxicity was evaluated by Lorke's method. Forced swimming test (FST) was performed for determining antidepressant property. The antioxidant potentials were performed by DPPH scavenging assay, ferric reducing antioxidant potential (FRAP) and Fe2+ ion chelating ability methods. Results: In acute toxicity study, JMO showed toxic effects within 5 minutes and estimated LD50 value was 2070.4 µl/kg body weight after 10 days oral treatment. The brine shrimp lethality assay exhibited concentration-dependent approach and the LC50 value was determined to be 139.73 l/ml, with lower and upper limits of 82.2428 l/ml and 202.7082 l/ml, respectively. In the FST method, intraperitoneal injections of JMO emulsion at doses of 78l/kg, 156l/kg, and 225l/kg of body weight resulted in a significant (p<0.005) increase in struggling time and a reduction in immobility. This observation had a nearly identical effect to the reference drug. Besides, JMO showed weak antioxidant activity in DPPH assay with an IC50 of 72.58±6.16387 μl/ml. But in other two methods, it exhibited strong antioxidant abilities whereas 1.4010 μl/ml reducing power for FRAP assay and 66.66% chelating rate for Fe2+ ion chelating ability test at 100 μl/ml concentration. Conclusion: The investigation clearly showed that JMO have significant antidepressant and cytotoxic properties whereas acute toxicity was moderate. Besides, JMO also possess considerable antioxidant activities.